Assisting consumers in detecting fake reviews: The role of identity information disclosure and consensus. (September 2016) - Munzel, Andreas
Abstract: Current discussions in academia and in the press increase consumers' awareness of potentially deceptive online reviews. The increasing practice of fake reviews posted online not only jeopardizes the credibility of review sites as important information sources for individuals but also endangers a valuable source of information for service providers. Two studies shed further light on the role of consensus and identity-related information in assisting consumers detect potentially faked reviews. In one preliminary study, a sample of 4826 rejected and 4881 published online reviews was analyzed to investigate the differences in the disclosure of author-related information such as name and age as well as star ratings across those reviews. In the main study, a 3 (identity disclosure) x 2 (consensus) x 2 (priming of fake reviews) experiment was carried out with 390 respondents. The results highlight the relevance of the review's consensus in relation to the overall rating of previous reviews and corroborate the results of the preliminary study from the perspective of an internet user: the value of the amount of available information on the review's author in assisting individuals detect potential fake reviews. This study complements research in computer science by highlighting the relevance of contextual—in addition to textual—indicators that assist internet users in detecting potentially deceptive online reviews.